Penguatan Peer Counseling bagi Konselor Sebaya di SMA N 6 Semarang - Devina Puspa Wulandari; Laura Khattrine Noviyanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Strengthening peer counseling is an effective approach in supporting mental health and psychosocial well-being of adolescents. Peer counseling allows individuals with similar backgrounds to share experiences, provide emotional support, and improve problem-solving skills. This study aims to see the effectiveness of peer counseling empowerment programs in improving psychological well-being and social skills of participants. The method used in this study was a literature study and an experiment with a control group of 32 participants. The results of this study were P <0.05, namely P = 0.028 with an average effectiveness result of 5.51%. which confirms that strengthening peer counseling is a strategy that can be applied in educational and community environments to improve adolescent mental well-being.